The yield of structural magnetic resonance imaging in autism spectrum disorders - Lisy, Jiri; Efremova, Andrea; Hrdlicka, Michal (Biomedical papers, 2019)
Aims: The aim of our study was to assess the yield of routine brain magnetic resonance imaging (MRI) performed at our hospital as part of the diagnostic procedures focused on autism. Methods: Our retrospective study involved children who had attended a diagnostic examination focused on autism and underwent brain MRIs between 1998-2015. The International Classification of Diseases, 10th edition was used to make clinical diagnoses. In 489 children (404 boys, 85 girls; mean age 8.0±4.2 years), a diagnosis of a pervasive developmental disorder was confirmed. Forty-five children, where the autism diagnosis was ruled out (but other psychiatric diagnoses found), served as a control group (36 boys, 9 girls; mean age 7.0±2.4 years). We can assume that in such a control group, brain abnormalities might occur at a higher frequency than in truly healthy children which would have the effect of reducing the difference between the groups. Results: MRI pathologies were more common in the autistic (45.4 %) compared to the control group (31.8%) but the difference was significant only at the trend level (P=0.085). Hypoplasia of the corpus callosum (CC) was significantly more common in the autistic vs. the control group (13.7 vs. 0%; P=0.009). In contrast, nonmyelinated areas of white matter were significantly more common in controls (31.8 vs.17.3%; P=0.018). Differences in other parameters were not significant. Conclusion: The occurrence of CC hypoplasia on routine MRI scans could represent a "red flag" for suspicion of autism.
Keywords: autism spectrum disorders; MRI; brain; corpus callosum